Prediction of diacerein inhibition activity against interleukin-1 receptors through docking method and tracing of pharmacokinetic profiles and their toxicity - Frengki Frengki; Vivi Sofia; Deddi Prima Putra; Fatma Sri Wahyuni; Daan Khambri; Henni Vanda (Pharmaciana, 2020)
IL-1 is one of the cytokines involved in joint diseases such as osteoarthritis. IL-1 plays a role in maintaining the balance of proteolytic proteins:MMPs and TIMPs inhibitors. Increased expression and uncontrolled IL-1 activity tend to increase the role of MMPs in degrading proteoglycans and joint tissue collagen. This study aims to reveal the interaction model of one of the osteoarthritis drugs, namely diacerein. A drug belongs to a group of disease-modifying osteoarthritis drugs (DMOADs) to suppressthe development of the disease rate, improving the structure and function of the cartilage and surrounding tissue. "In silico" digital test uses the technique of "molecular docking: used as a method of the approach using the MOE 2007.09 software application. The test material was in the form of a diacerein 3D structure and five control ligands, while the IL-1Î² / IL-1RI receptor template was downloaded from pdb.org (PDB ID: 1ITB). The ligand pharmacokinetic profile will also be displayed obtained through the ADMETSAR server. The docking results showed diacerein had the lowest docking score of -12.3285 kcal/mol with the strongest affinity, the best pharmacokinetic profile but more toxic. This study proves that the mechanism of diacerein inhibition of IL-1Î² / IL-1RI receptors is similar to dexamethasone, prednisolone,and minocycline.